Implementasi Metode Active Learning dalam Pengalaman Belajar dan Keaktifan Siswa pada Pembelajaran Aqidah Akhlak di Mts Pertanian Kota Madiun - Safingil Anam (Program Studi Pendidikan Guru Madrasah Ibtidaiyah INSURI Ponorogo, 2024)
This study aims to describe the implementation of the active learning method in Aqidah Akhlak learning at MTs Pertanian Kota Madiun and to analyze its impact on students’ learning experiences and activeness. The urgency of this research lies in the need for learning methods that foster student engagement and create meaningful learning experiences in Aqidah Akhlak. Using a descriptive qualitative approach with observations, interviews, and documentation, data were gathered from the head of the madrasah, the vice principal for curriculum, Aqidah Akhlak teachers, and students. The findings show that active learning was implemented through group discussions, question-and-answer sessions, and presentations, with teachers acting as facilitators to guide student participation. This method effectively encourages active involvement, increases motivation, enthusiasm, and confidence, and develops students’ critical thinking skills while promoting collaborative learning. Therefore, active learning is considered effective in enhancing students’ learning experiences and engagement in Aqidah Akhlak learning at MTs Pertanian Kota Madiun.